Preductal postductal oxygen saturation gradient in preterm infants immediately after birth: Effect of gestational age on achievement of target saturation - Shaon Mitra,; Arnab Mondal, (Asian Journal of Medical Sciences, 2023)
Background: The delivery room oxygen saturation (SpO2) monitoring in neonates is based on studies in term infants. Study of preductal-postductal SpO2 gradient in healthy preterms immediately after birth will help in follow-up of an abnormal gradient, rationalizing oxygen therapy, and early identification of congenital cyanotic heart disease. Aims and Objectives: SpO2 is initially low and gradually increases to normal in healthy term newborns postnatally. Postductal SpO2 is lower than preductal, but their difference gradually decreases postnatally. Our study aims to find out the preductal-postductal SpO2 gradient in healthy preterms and the correlation between gestational age and SpO2. In preterms, gradient may persist longer due to patent ductus arteriosus and higher pulmonary vascular resistance. Materials and Methods: This observational cross-sectional study has been conducted over 1 year with 80 preterms immediately after birth, after the Institutional Ethics Committee approval and parental informed consent. Preductal and postductal SpO2 were recorded by probes on right hand and left foot respectively for 20 min after birth. Data were analyzed by SPSS software. Results: This study shows that preductal-postductal SpO2 gradient is significant in the first 20 min of life in preterms, and there is significant positive correlation of gestational age with preductal SpO2 at 1 min and negative correlation of gestational age with time taken to achieve 90% SpO2. Conclusion: This study concludes that significant preductal-postductal SpO2 gradient persists for first 20 min of life in preterms and preductal SpO2 at 1 min decreases and time taken to reach SpO2 90% increases significantly with decreasing gestational age.